Long-term efficacy and safety of α1 proteinase inhibitor treatment for emphysema caused by severe α1 antitrypsin deficiency: an open-label extension trial (RAPID-OLE). Issue 1 (January 2017) - McElvaney, Noel G; Burdon, Jonathan; Holmes, Mark; Glanville, Allan; Wark, Peter A B; Thompson, Philip J; Hernandez, Paul; Chlumsky, Jan; Teschler, Helmut; Ficker, Joachim H; Seersholm, Niels; Altraja, Alan; et al.
Summary: Background: Purified α1 proteinase inhibitor (A1PI) slowed emphysema progression in patients with severe α1 antitrypsin deficiency in a randomised controlled trial (RAPID-RCT), which was followed by an open-label extension trial (RAPID-OLE). The aim was to investigate the prolonged treatment effect of A1PI on the progression of emphysema as assessed by the loss of lung density in relation to RAPID-RCT. Methods: Patients who had received either A1PI treatment (Zemaira or Respreeza; early-start group) or placebo (delayed-start group) in the RAPID-RCT trial were included in this 2-year open-label extension trial (RAPID-OLE). Patients from 22 hospitals in 11 countries outside of the USA received 60 mg/kg per week A1PI. The primary endpoint was annual rate of adjusted 15th percentile lung density loss measured using CT in the intention-to-treat population with a mixed-effects regression model. This trial is registered withClinicalTrials.gov, numberNCT00670007 . Findings: Between March 1, 2006, and Oct 13, 2010, 140 patients from RAPID-RCT entered RAPID-OLE: 76 from the early-start group and 64 from the delayed-start group. Between day 1 and month 24 (RAPID-RCT), the rate of lung density loss in RAPID-OLE patients was lower in the early-start group (−1·51 g/L per year [SE 0·25] at total lung capacity [TLC]; −1·55 g/L per year [0·24] at TLC plus functional residual capacity [FRC]; and −1·60 g/L per year [0·26] at FRC) than in the delayed-start group (−2·26 g/L per year [0·27] at TLC; −2·16 g/L per year [0·26] at TLC plus FRC, and −2·05 g/L per year [0·28] at FRC). Between months 24 and 48, the rate of lung density loss was reduced in delayed-start patients (from −2·26 g/L per year to −1·26 g/L per year), but no significant difference was seen in the rate in early-start patients during this time period (−1·51 g/L per year to −1·63 g/L per year), thus in early-start patients the efficacy was sustained to month 48. Interpretation: RAPID-OLE supports the continued efficacy of A1PI in slowing disease progression during 4 years of treatment. Lost lung density was never recovered, highlighting the importance of early intervention with A1PI treatment. Funding: CSL Behring.